Aging reduces the toxicity of pristine but not sulphidised silver nanoparticles to soil bacteria - Schultz, Carolin L; Gray, Joanna; Verweij, Rudo A; Busquets-Fité, Martí; Puntes, Victor; Svendsen, Claus; Lahive, Elma; Matzke, Marianne (Environmental science. Nano, 2018)
In the environment engineered nanoparticles (ENPs) are subject to chemical and physical transformation processes. Thus, to understand their impact, it is important to consider how bioavailability and toxicity are influenced by these "aging" transformations with relation to environmental conditions and ENP properties. Here, two soil bacteria were exposed to Ag ENPs in ISO media (± fulvic acid) and soil pore water extracts with pH 6 and pH 8. The ENPs tested were 49 nm unfunctionalised, citrate stabilised (Ag-citr), 58 nm PVP-coated (Ag-PVP) and 36 nm sulphidised (Ag 2 S-PVP); AgNO 3 was used as a positive control. Exposures were carried out using pristine (unaged) and 24 h aged ENPs, and the 24 h soluble fraction. Overall, toxicity was ranked AgNO 3 > Ag-PVP ≥ Ag-citr > Ag 2 S. Aging of AgNO 3 , Ag-PVP and Ag-citr in the ISO medium caused little change from unaged exposures and growth inhibition was mainly caused by soluble silver. Added fulvic acid decreased silver toxicity after aging and reduced the contribution of dissolution; as was the case in the soil pore waters where toxicity could not be attributed to ionic silver. Ag 2 S toxicity to A. globiformis in both ISO variants increased after aging, yet followed the same patterns as the metallic ENPs in the pore waters. For all ENPs pH effects were species dependent. Together this data showed that aging reduced toxicity in media with organic matter and despite soluble silver being the main driver of pristine ENP toxicity in the standard ISO medium, dissolution did not fully explain toxicity in the presence of organic matter. Aging of silver nanoparticles shows soluble silver driving toxicity in ISO medium, but not in media containing natural organic matter.